DEVELOPMENT OF CREATIVE COMPETENCES OF TECHNOLOGICAL EDUCATION TEACHERS IN TRADITIONAL AND MODERN EDUCATION. (International journal of artificial intelligence, 2025)
This article analyzes the issues of developing creative competencies of technological education teachers in traditional and modern education systems. Effective ways to develop teachers' creative competencies through the use of modern educational technologies and methods are considered, including design, problem-based learning, group work, interactive methods, and the use of ICT. In addition, the importance of the educational environment in developing teachers' creativity, the promotion of independent thinking in the learning process, the use of creative tasks, and the application of innovative approaches are highlighted.